Engineering response of biomedical grade isotactic polypropylene reinforced with titanium nitride nanoparticles for material extrusion three-dimensional printing - Nikolaos Michailidis; Markos Petousis; Amalia Moutsopoulou; Apostolos Argyros; Ioannis Ntintakis; Vassilis Papadakis; Nektarios K. Nasikas; Nectarios Vidakis (European Journal of Materials, 2024)
Herein, a new generation of printable bio-composite nanofilaments is explored. The aim was to explore the efficiency of Titanium nitride (TiN) as a reinforcing agent for the Fused Filament Fabrication (FFF) 3D printing technique. TiN, a common ceramic in medical devices, in nanopowder form, was used as a polymer enhancer for the also popular medical devices polypropylene thermoplastic. Such filaments with superior performance are needed for demanding applications, in which common polymers do not meet the specifications. To fully comprehend the material qualities and behaviour, a variety of tests, including mechanical testing, thermal and rheological investigation, and spectroscopic analysis, were carried out following standards. The effect of the filler percentage was also considered. The morphological properties of the materials were also assessed. The mechanical response of the nanocomposite with a ‑2.0 wt. % filler concentration showed the best improvements in all experiments conducted, including tensile (41.5%), flexural (33.7%), and impact (18.0%) strength. The microhardness was improved 44.8% by the 2.0 wt. % filler concentration nanocomposite. Overall, the efficiency of TiN as a reinforcement agent in FFF 3D printing was proven, making the proposed nanocomposites a sufficient solution when improved performance is required.